1995
DOI: 10.1074/jbc.270.7.3056
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylsphingosine (C2--ceramide) Inhibited Neutrophil Superoxide Formation and Calcium Influx

Abstract: Ceramide, a product arising from sphingomyelinase activity, has been shown to act as an intracellular second messenger in effecting growth inhibition, cellular differentiation, and apoptosis. In the present study, the relative effects of cell-permeable ceramides, N-acetylsphingosine (C2-ceramide) and N-hexanoylsphingosine (C6-ceramide), on neutrophil responses were measured. When cells were activated with fMet-Leu-Phe, C2-ceramide both potentiated (< 1 microM) and inhibited (> 1 microM) superoxide generation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 31 publications
4
38
0
Order By: Relevance
“…Several lines of evidence have indicated that short-chain Cer, which could mimic natural Cer, evoke various physiological effects in different types of cell [1][2][3][4][5]. The most important finding of this study was that short-chain Cer could be converted to short-chain gangliosides GM3 in intact cells.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Several lines of evidence have indicated that short-chain Cer, which could mimic natural Cer, evoke various physiological effects in different types of cell [1][2][3][4][5]. The most important finding of this study was that short-chain Cer could be converted to short-chain gangliosides GM3 in intact cells.…”
Section: Discussionmentioning
confidence: 73%
“…For example, C2-and C6-Cer have been shown to induce cell differentiation [1] and programmed cell death [2], to mediate EGF receptor phosphorylation [3] and endocytosis [4], and to inhibit neutrophil superoxide formation and calcium influx [5]. However, there have been very few reports about the intracellular metabolism of these synthetic short-chain Cer.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying this behavior is unclear, although similar effects have also been seen in other cell types. Hence, studies describing the regulation of fMLP-induced superoxide anion generated by neutrophils found that C 2 at concentrations below 1 M potentiated the generation of this reactive species, whereas at concentrations greater than 1 M inhibited its production (40). In addition, the ability of ceramide to activate and phosphorylate protein kinase C , an atypical protein kinase C isoform, has been shown to be bifunctional (33).…”
Section: Ceramide Leads To Generation Of Reactive Oxygen Species In Imentioning
confidence: 99%
“…Direct evidence for a role of ceramides in signal transduction has come from studies using exogenous sphingomyelinase and cell-permeable ceramides to duplicate receptor-mediated activation. Sphingomyelinase and short chain ceramides have been used to implicate ceramides in such diverse processes as apoptosis, Ca 2ϩ influx, superoxide generation, proliferation, and cell cycle regulation (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%